Improving Cervical Cancer Awareness Among Reproductive-Age Couples:An Educational Approach Using Visual Inspection with Acetic Acid (IVA) - Haryono, Nathasia; Siregar, Wilda Wahyuni; Octavariny, Raisha; Kurniawati, Kurniawati; Aula, Khomaina (JURNAL PENGMAS KESTRA (JPK), 2025)
Cervical cancer is one of the leading causes of death among women in developing countries, primarily due to delays in early detection. According to data from the World Health Organization, there are more than 342,000 cervical cancer-related deaths each year, with 90% of these cases occurring in low- and middle-income countries. In Indonesia, cervical cancer ranks as the second most common cancer after breast cancer, with over 36,000 new cases annually and a death toll reaching 18,000. Visual Inspection with Acetic Acid (IVA) is a simple and affordable screening method that can be performed at primary healthcare facilities. This community service activity aims to increase the knowledge, attitudes, and readiness of couples of reproductive age (CoRA) in conducting early detection of cervical cancer through family-based education. The activity was carried out using lectures supported by media such as leaflets and videos. A total of 30 CoRA participants from the Sukorame health center area took part in the program. The education was delivered through lectures, interactive discussions, and educational video screenings. The education on VIA screening for couples of reproductive age proved effective in improving their understanding, attitudes, and readiness to carry out early detection of cervical cancer. Prior to the education, most participants lacked awareness about the importance of VIA screening. However, after the session, there was a significant increase in knowledge (86.67%), willingness to undergo screening (66.67%), and shared awareness between partners (60%) about the importance of early detection.This interactive and contextual educational approach was effective in building awareness and encouraging preventive action at both family and community levels.